Conductive pnipam ionic gel applied to wearable sensing devices

CN117736367BActive Publication Date: 2026-10-30AFFILIATED HOSPITAL OF JIANGNAN UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311490044.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-09
Publication Date
2026-10-30
Estimated Expiration
2043-11-09

AI Technical Summary

Technical Problem

[0005]本发明解决了传统PNIPAM水凝胶力学性质较弱,无法应用于可穿戴生物传感设备的问题,设计了PNIPAM离子凝胶,增强了材料的导电性、力学性质、生物相容性,在用于身体粘附信号检测的可穿戴生物传感器方面有着巨大潜力

Benefits of technology

[0025]本发明在传统PNIPAM水凝胶的基础上引入了离子液体,增强了材料的导电性、力学性质、生物相容性,可以检测到身体粘附信号。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117736367B_ABST
    Figure CN117736367B_ABST
Patent Text Reader

Abstract

The application discloses a kind of electrically conductive PNIPAM ion gel applied to wearable sensing device, belong to biomedical gel material field. Including the following steps: (1) take ion liquid (1-butyl-3-methyl imidazole) dissolved in water, and prepare ion liquid mixture liquid;(2) monomer 2-acrylamido-2-methylpropane sulfonic acid and N-isopropyl acrylamide are added to the ion liquid mixture liquid prepared in step (1), and reaction liquid is prepared;(3) crosslinking agent N,N'-methylene bisacrylamide and initiator L-sodium ascorbate are added to the reaction liquid prepared in step (2), and electrically conductive PNIPAM ion gel is obtained by reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a conductive PNIPAM ionogel for wearable sensing devices, belonging to the field of biomedical gel materials. Background Technology

[0002] Materials whose properties can be adjusted according to environmental factors such as temperature, pH, and ionic strength are rapidly developing and are known as smart materials. Hydrogels formed from smart polymers have a variety of applications. Among smart polymers, the thermoresponsive polymer poly(N-isopropylacrylamide) (PNIPAM) is particularly important because it has a well-defined structure and properties, especially its temperature response, which is closed to the human body and can be finely tuned. Mechanical properties are crucial for the performance of stimulus-responsive hydrogels in various applications. However, natural PNIPAM hydrogels are very fragile and are rarely used for any practical purpose.

[0003] Conductive poly(N-isopropylacrylamide) hydrogel (PNIPAM hydrogel) is an ideal building block for fabricating soft electronic devices and wearable biosensors due to its rapid temperature response. However, its poor mechanical properties, conductivity, and adhesion limit its application in wearable biosensors. To overcome this problem, the ionic liquid chloride (1-butyl-3-methylimidazolium) was introduced into the system to prepare PNIPAM ionic gel. This ionic gel can protect the free radicals generated during gelation, accelerate the gelation process, and improve the mechanical properties and biocompatibility of the material. It has great potential for wearable biosensors for detecting body adhesion signals. Summary of the Invention

[0004] Technical issues

[0005] This invention addresses the problem that traditional PNIPAM hydrogels have weak mechanical properties, making them unsuitable for wearable biosensor devices. It designs a PNIPAM ionogel that enhances the material's conductivity, mechanical properties, and biocompatibility, showing great potential for wearable biosensors used for detecting body adhesion signals.

[0006] Technical solution

[0007] To address the above problems, this invention provides a method for preparing a conductive PNIPAM ionogel with mechanical strength, comprising the following steps:

[0008] (1) Dissolve the ionic liquid chloride (1-butyl-3-methylimidazolium) in water to prepare an ionic liquid mixture;

[0009] (2) Add monomers 2-acrylamido-2-methylpropanesulfonic acid and N-isopropylacrylamide to the ionic liquid mixture prepared in step (1) to obtain a reaction solution;

[0010] (3) Add crosslinking agent N,N'-methylenebisacrylamide and initiator L-sodium ascorbate to the reaction solution obtained in step (2) and react to obtain conductive PNIPAM ion gel.

[0011] Furthermore, in step (1), the mass ratio of chlorine (1-butyl-3-methylimidazolium) to water is 30-50:100.

[0012] Preferably, in step (1), the mass ratio of chlorine (1-butyl-3-methylimidazolium) to water is 40:100.

[0013] Furthermore, in step (2), the molar ratio of monomers 2-acrylamido-2-methylpropanesulfonic acid and N-isopropylacrylamide is 1:10 to 20.

[0014] Preferably, in step (2), the molar ratio of monomer 2-acrylamido-2-methylpropanesulfonic acid and N-isopropylacrylamide is 1:16.

[0015] Furthermore, in step (2), the total mass ratio of monomers 2-acrylamido-2-methylpropanesulfonic acid and N-isopropylacrylamide to the mass ratio of the ionic liquid mixture is 10-30:100.

[0016] Preferably, in step (2), the total mass ratio of monomers 2-acrylamido-2-methylpropanesulfonic acid and N-isopropylacrylamide to the mass ratio of the ionic liquid mixture is 20:100.

[0017] Furthermore, in step (3), the concentration of the crosslinking agent N,N'-methylenebisacrylamide in the reaction solution is 1-5 mg / mL.

[0018] Preferably, in step (3), the concentration of the crosslinking agent N,N'-methylenebisacrylamide in the reaction solution is 3 mg / mL.

[0019] Furthermore, in step (3), the concentration of the initiator L-ascorbic acid sodium in the reaction solution is 3 to 9 mg / mL.

[0020] Preferably, in step (3), the concentration of the initiator sodium L-ascorbate in the reaction solution is 6 mg / mL.

[0021] Furthermore, the reaction described in step (3) is allowed to stand at 20–25°C for 1.5–2 hours.

[0022] The present invention provides a conductive PNIPAM ionogel with mechanical strength prepared by the above method.

[0023] The present invention provides the application of conductive PNIPAM ion gel with mechanical strength in the fields of medical device manufacturing and biosensors.

[0024] Beneficial effects

[0025] This invention introduces ionic liquids into the traditional PNIPAM hydrogel, which enhances the material's conductivity, mechanical properties, and biocompatibility, and enables the detection of body adhesion signals. Attached Figure Description

[0026] Figure 1 The infrared spectra of each gel material are shown.

[0027] Figure 2 The diagram shows the gelation process of each gel material.

[0028] Figure 3 The UV spectra of each gel material are shown.

[0029] Figure 4 The amplitude scan diagrams for each gel material are shown.

[0030] Figure 5 The stretch curves of each gel material are shown.

[0031] Figure 6 Compression curves for each gel material.

[0032] Figure 7 The diagram shows the adhesion properties of each gel material.

[0033] Figure 8 The electrochemical impedance spectroscopy (EIS) spectra of each gel are shown.

[0034] Figure 9 The images show the biocompatibility of various gel materials. a is the CCK8 result image, b is a confocal photograph, c is a skin sensitization photograph, and d is an HE-stained section image (arrows indicate the location of the gel).

[0035] Figure 10 This is a schematic diagram of the conductivity of the target ionogel and a graph showing the change in relative resistance with joint movement. Detailed Implementation

[0036] Source of raw materials

[0037] N-Isopropylacrylamide (NIPAM, 99%) was purchased from Thermo Scientific; (1-Butyl-3-methylimidazolium chloride) ([BMIm][Cl]), 99%) was purchased from Aladdin; 2-Acrylamido-2-methylpropanesulfonic acid (AMPS, 99%) was purchased from Macklin; N,N'-Methylenebisacrylamide (NNMBA, 98%) was purchased from Bailingwei; and L-Ascorbic acid sodium (ASA, 99%) was purchased from Macklin.

[0038] Example 1

[0039] A method for preparing a conductive PNIPAM ionogel with enhanced mechanical properties:

[0040] (1) Preparation of ionic liquid and deionized water mixture: Dissolve ionic liquid (ILs) chloride (1-butyl-3-methylimidazolium) ([BMIm][Cl]) in deionized water (DIW) with a mass ratio of IL / DIW of 40 w / w% to obtain ionic liquid mixture.

[0041] (2) Add the main monomer NIPAM: Add monomers 2-acrylamido-2-methylpropanesulfonic acid (AMPS) and N-isopropylacrylamide (NIPAM) to the mixture in (1) at a molar ratio of 1:16. The total mass ratio of AMPS and NIPAM monomers to the ionic liquid mixture is 20w / w%. Sonicate in an ultrasonic machine for 30s to fully dissolve the monomers in the mixture to obtain the reaction solution.

[0042] (3) Add crosslinking agent NNMBA and initiator ASA to form a gel: Add crosslinking agent N,N'-methylenebisacrylamide (NNMBA) to the reaction solution of (2), with a concentration of 3 mg / mL in the reaction solution. Finally, add initiator L-ascorbic acid sodium (ASA), with a concentration of 6 mg / mL in the reaction solution. The resulting mixed solution is sonicated in an ultrasonic machine for 1 min and left to stand at room temperature for 2 h to form a conductive PNIPAM ion gel.

[0043] Comparative Example 1

[0044] Gels were prepared according to the various gel component ratios in Table 1, and then tested.

[0045] Table 1. Gel composition ratio

[0046]

[0047] The preparation of PNIPAM hydrogel was carried out according to the preparation steps of Example 1, except that step (1) was omitted, while the other steps and parameters remained unchanged.

[0048] The comparative preparation of other PNIPAM ionogels was carried out according to the preparation steps of Example 1, except that the IL / DIW mass ratio in step (1) was changed to 20w / w%, 60w / w%, and 80w / w, respectively.

[0049] Example 2

[0050] This example presents the infrared spectra of various gels obtained in Example 1:

[0051] Figure 1 The infrared spectra of each gel were recorded using an FTIR spectrometer system. As shown in the figure, the 1631 cm⁻¹... -1 The characteristic peak of the imide group is 1167 cm⁻¹. -1 The peak at 619 cm⁻¹ represents the CN stretching vibration of alkyl groups. -1 The peak at this location corresponds to the C-Cl stretching vibration, consistent with literature records, indicating the synthesis of the target PNIPAM hydrogel and PNIPAM ionogel.

[0052] Example 3

[0053] This example shows photographs of the gelation process of various gels obtained in Example 1. Figure 2 The results show that the gelation speed of the PNIPAM ionogel group after the introduction of ionic liquid is significantly improved compared with that of the PNIPAM hydrogel.

[0054] Example 4

[0055] This example shows the UV absorption spectra of methylene blue solutions for various gels obtained in Example 1:

[0056] Figure 3 The UV absorption spectra of methylene blue solutions for each gel were recorded using a UV spectrometer system. Literature indicates that OH radicals can react with methylene blue. The figure shows that, compared to the control group, the reaction only started after the addition of ASA, indicating that ASA acts as the initiator. The methylene blue absorption peak at 668 nm was significantly lowered, indicating the generation of OH radicals. The introduction of ionic liquids provides some protection against the generated OH radicals, thereby extending the chain reaction and accelerating gel formation.

[0057] Example 5

[0058] This example tests the rheological properties of various gels obtained in Example 1:

[0059] (1) The gel is placed in a circular parallel plate with a diameter of 12 mm and a gap of 1 mm;

[0060] (2) The rheological characterization of the gel was performed using a rheometer. For amplitude scanning, tests were conducted at a constant temperature of 37°C and a strain range of 0.1% to 100%.

[0061] Figure 4 The image shows the amplitude scan of the gel material prepared in Example 1. Analysis reveals that as the concentration of the ionic liquid in the sample increases, the mechanical properties of the sample first strengthen and then weaken, but overall, the strength of the PNIPAM ionic gel is higher than that of the PNIPAM hydrogel.

[0062] Example 6

[0063] This example tests the mechanical properties (tensile, compression, adhesion) of various gels obtained in Example 1:

[0064] (1) Tensile properties: A hydrogel with a length of 25 mm, a width of 10 mm, and a thickness of 1 mm was tested using a general testing machine at 50 mm min. -1 The tensile speed was measured to obtain the tensile curve.

[0065] (2) Compression performance: Cylindrical gels with a diameter of 10 mm and a height of 12 mm were prepared and tested using a general-purpose testing machine at 10 mm min. -1 The compression curve was determined at a constant rate.

[0066] (3) Adhesion: The adhesive properties of the gel were studied by standard overlap shear test on a general-purpose testing machine equipped with a 2kN force sensor. Samples used for the overlap shear test were prepared by adhering two substrates (pigskin) to a thin square gel with a length of 20 mm, a width of 10 mm, and a thickness of 1 mm, with an overlap area of ​​20 cm². 2 Before testing, apply a force (100g) for 10 seconds to bond it, and all tests are performed at 10mm min. -1 The stretching is performed at a constant speed.

[0067] By comparison Figure 5 , 6 Data from sets 7 and 8 show that the addition of ionic liquid significantly improves the performance of PNIPAM ionic gel compared to PNIPAM hydrogel.

[0068] Example 7

[0069] This example tests the conductivity of various gels obtained in Example 1:

[0070] Electrochemical impedance spectroscopy (EIS) measurements were performed using an electrochemical workstation with an open-circuit potential of 0.1 V and a scan range of 100 kHz to 0.1 Hz. A gel measuring 8 mm long, 9 mm wide, and 2 mm thick was placed between two platinum electrodes (10 mm x 10 mm) within a custom-made quartz cuvette and surrounded by PBS buffer solution. An Ag / AgCl electrode (containing 3 mg KCl) was used as the reference electrode.

[0071] Figure 8 The electrochemical impedance spectroscopy of each gel shows that the conductivity of the material is significantly improved when the IL / DIW mass ratio is 40 w / w%.

[0072] Considering various properties, the ionogel with an IL / DIW mass ratio of 40 w / w% exhibits the best properties. Therefore, this ratio was set as the target ionogel for subsequent testing.

[0073] Example 8

[0074] This example is for testing the biocompatibility of various gels obtained in Example 1:

[0075] (1) In vitro cell biocompatibility: First, MEF cells (mouse embryonic fibroblasts) were cultured overnight in culture dishes to allow cell adhesion. Then, the cells were co-incubated with gel for 1 day and 2 days, with phosphate-buffered saline (PBS) as a negative control. CCK-8 assay was used to quantify relative cell viability after 1 and 2 days of co-culture. Cell morphology was observed by confocal laser scanning microscopy after calcein-AM / PI staining.

[0076] (2) Skin irritation test: A skin irritation test was conducted on rats (SD rats) to determine the skin irritability of the gel. The gel sample was cut into slices with a diameter of 15 mm and a thickness of 2 mm. The weight of the PBS cotton pads was the same as that of the gel. The rats were anesthetized with isoflurane, and then the hair on the back of the rats was shaved to obtain bare skin. The hydrogel material to be tested was applied to the skin and kept for 24 h. After that, the material was removed and the observations were recorded at 1 h, 24 h, 48 h and 72 h. PBS and SDS were used as negative control materials and positive control materials, respectively. Three parallel groups were set up, with one rat in each group.

[0077] (3) Subcutaneous sensitization experiment: Rats (SD rats) were anesthetized with isoflurane. The hair on the back of the rats was clamped with an electric shaver, and the villi were further removed with depilatory cream. The gel sample was cut into slices with a diameter of 15 mm and a thickness of 2 mm. Then, the experimental area was divided into four groups, including a PBS negative control group, a PNIPAM hydrogel group, an IL / DIW-20 w / w% iontophoresis gel group, and an IL / DIW-40 w / w% iontophoresis gel group. An incision was made on the skin surface of the rat's back, and the corresponding material was inserted. Two parallel groups were set up, with incision times of 1 week and 3 weeks, respectively. After the expiration, the rats were sacrificed, and the skin above the gel was peeled off and sent for HE staining and sectioning.

[0078] Figure 9 The images show the results of various biocompatibility experiments. 9a is the CCK8 result image, 9b is a confocal photograph, 9c is a photograph of skin sensitization, and 9d is an HE-stained section image (arrows indicate the location of the gel). Analysis shows that the PNIPAM ionomer gel did not exhibit significant cytotoxicity or skin sensitization compared to the control group in cell and animal experiments, and its biocompatibility was improved compared to the PNIPAM hydrogel.

[0079] Example 9

[0080] This embodiment tests the application of the target ionogel in wearable biosensors:

[0081] Motion signals were recorded using ionogel sensors, which were then attached to finger and wrist joints. The sensors were subsequently connected to an electrochemical workstation, and current changes were recorded using amperometric curve software. The voltage was fixed at 0.1V, and the sampling interval was set to 0.1 or 0.2 s.

[0082] Figure 10 This diagram illustrates the conductivity of the target ionogel and the change in relative resistance with joint movement. Analysis shows that the target ionogel exhibits good conductivity and has potential applications in wearable biosensors.

[0083] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing a conductive PNIPAM ionogel with mechanical strength, characterized in that, Includes the following steps: (1) Dissolve the ionic liquid chloride (1-butyl-3-methylimidazolium) in water to prepare an ionic liquid mixture; the mass ratio of chloride (1-butyl-3-methylimidazolium) to water is 30~50:100; (2) Add monomers 2-acrylamido-2-methylpropanesulfonic acid and N-isopropylacrylamide to the ionic liquid mixture prepared in step (1) to obtain a reaction solution; the molar ratio of monomers 2-acrylamido-2-methylpropanesulfonic acid and N-isopropylacrylamide is 1:10~20; the total mass of monomers 2-acrylamido-2-methylpropanesulfonic acid and N-isopropylacrylamide to the mass ratio of the ionic liquid mixture is 10~30:100; (3) Add crosslinking agent N,N'-methylenebisacrylamide and initiator L-sodium ascorbate to the reaction solution obtained in step (2), and react to obtain conductive PNIPAM ion gel.

2. The preparation method according to claim 1, characterized in that, In step (1), the mass ratio of chlorine (1-butyl-3-methylimidazolium) to water is 40:

100.

3. The preparation method according to claim 1, characterized in that, In step (3), the concentration of the crosslinking agent N,N'-methylenebisacrylamide in the reaction solution is 1~5 mg / mL.

4. The preparation method according to claim 1, characterized in that, In step (3), the concentration of the initiator sodium L-ascorbate in the reaction solution is 3~9 mg / mL.

5. The preparation method according to claim 1, characterized in that, The reaction described in step (3) is to stand at 20~25℃ for 1.5~2 h.

6. A conductive PNIPAM ionogel with mechanical strength prepared by the preparation method according to any one of claims 1 to 5.

7. The application of the conductive PNIPAM ionogel with mechanical strength as described in claim 6 in the fields of medical device manufacturing and biosensors.